An Error Analysis Student’s Writing Descriptive Text At Junior High School: Analisis Kesalahan Penulisan Teks Deskriptif Siswa Di Sekolah Menengah Pertama - Virny Melisa Irwandi; Dian Rachma Santoso (Universitas Muhammadiyah Sidoarjo, 2020)
Error analysis is one of method to help the teacher in teaching and learning languange , not only in English but in other languagesince the teacher will observe the reason or context why the mistakes are made by the students especially in writing. This error happened when the learners cannot correct themselves.Based on the experience of the writer, not every student at SMP PGRI 10 Candi write the text correctly, because some student in SMP PGRI 10 Candi translate Bahasa to English directly. This is mean that students are influenced by Bahasa patterns in writing. So, the writer wants to help the students at SMP PGRI 10 Candi write descriptive text better and appropriate with the generic structure. The aim of this study is to find out the types of error analysis by Dulay Theory and the dominant type of Surface Strategy Taxonomy in descriptive text that the student wrote. The types of error based on Surface Strategy Taxonomy are (1) Omission (2) Addition (3) Misformation (4) Misordeing. This study used qualitative research through content analysis method. This data was classified based on several criteria. From this study the researcher conlcluded that the dominant types of errors analysis is in misformation